Bacterial cellulose membranes as a potential drug delivery system for photodynamic therapy of skin cancer - Peres, Maristela F. S.; Nigoghossian, Karina [UNESP]; Primo, Fernando L. [UNESP]; Saska, Sybele [UNESP]; Capote, Ticiana S. O. [UNESP]; Caminaga, Raquel M. S. [UNESP]; Messaddeq, Younes [UNESP]; Ribeiro, Sidney J. L. [UNESP]; Tedesco, Antonio C. (Sociedade Brasileira de Quimica (SBQ), 2016)
The development of drug delivery systems for photodynamic therapy (PDT) is increasingly demanded due to the hydrophobicity presented by most of photosensitizers molecules. Bacterial cellulose (BC), a highly pure cellulose produced by bacteria, possesses the essential features for applications in drug delivery systems, such as large surface area and excellent loading capacity. BC membranes prepared containing a photosensitizer, chloroaluminum phthalocyanine (ClAlPc), were tested aiming applications as a drug delivery system for PDT skin cancer protocols. BC membranes production was optimized regarding thickness and optical transmission. Thinner membranes lead to higher relative incorporation efficiencies. Skin permeation and retention in vitro tests were performed by using pig's ears as a skin model. ClAlPc was retained at stratum corneum and epidermis/dermis, showing adequate properties for topical administration of ClAlPc. Photophysical studies showed that singlet oxygen production was not affected for ClAlPc compartmentalized in the BC array. BC-ClAlPc membranes did not present cytotoxic effects in vitro.
Keywords: Bacterial cellulose; Drug delivery system; Photodynamic therapy; Phthalocyanine